Chrześcijanie wobec bogactwa w nauczaniu Klemensa Aleksandryjskiego - Szczur, Piotr (Archiwa, Biblioteki i Muzea Kościelne, 2020)
In this article we present some statements of Clement of Alexandria (c. 150 – c. 212/215), in which he analyses a biblical pericope about the rich man from the Gospel according St. Mark (Mark 10,17-31; see also: Matthew 19,16-22, Luke 18,18-33). In a Clement’s point of view, the evangelical advice to renounce material riches should be interpreted in an allegorical way, because that advice says rather about desire and unstopped attachment to material riches than about money or material worth itself. Everything what happens inside human soul is much more important than outer state of being rich or poor. Saying about real material richness Clement points that such richness is an indispensable tool of making good, while sharing with material goods is a social and religious duty of rich people. Wealthy people should wisely use their richness, according to God’s plan and serving other Christians, while benefi ciaries in return should intercede and pray for the givers to God. Clement’s interpretation of evangelical pericope about the rich man is an important moment in a process of conciliating the economical elite of society with Christian community. It is also an effort to show the rich Christians their role and place in local Church.